Uji kerentanan keamanan pada web Sistem Informasi Akademik Satya Wacana menggunakan metode Vulnerability Assessment - Efendi, Rissal; Wahyono, Teguh; Widiasari, Indrastanti R. (Fakultas Teknologi Informasi Universitas Kristen Satya Wacana, 2024)
Vulnerability assessment is a process to look for system security gaps that can cause information technology process system failure. In carrying out a vulnerability assessment there are three main stages, namely information collection, assessment and exploit using the Greybone Openvas tool with a Full Scan template on the object and several credentials provided by a website. From the vulnerability assessment process, five vulnerabilities were found on assets, namely critical risk with a few 0, high risk with a few 2, medium risk with a few 2, and low risk with a few 1. Based on the conclusions from the vulnerability analysis the website and the results of identity verification, it was concluded that the website had a few weaknesses and vulnerabilities that needed to be fixed to maintain the security and quality of the website. Corrective actions on website configuration need to be taken such as setting cookies, SSL, HTTP headers, and others. SSL/TLS services do not accurately limit the renegotiation stage of the system, making it easier for attackers to carry out Denial of Service attacks by carrying out many renegotiations in one connection.